Analisis Gaya Hidup Hedonis Terhadap Impulsive Buying Dengan Promosi Sebagai Variabel Moderasi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Mataram yang Menggunakan Platform E-Commerce Shopee - Putri Lestari, Dwi; Ilhamuddin, M (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This study aims to analyze the influence of hedonistic lifestyle on impulsive buying behavior with promotion as a moderation variable in students of the Faculty of Economics and Business, University of Mataram (FEB UNRAM) who use the Shopee e-commerce platform. A hedonistic lifestyle is characterized by the pursuit of personal pleasure and satisfaction, which has the potential to influence impulsive purchasing decisions. This study uses a non-experimental quantitative method with data collection through questionnaires distributed to 100 respondents using purposive sampling techniques. Data processing was carried out using SMART PLS 4.0 for Windows, including validity tests, reliability tests, classical assumption tests, path analysis, and hypothesis testing. The results of the study show that the hedonistic lifestyle positively and significantly affects impulse purchases, which affects consumer perception of promotions offered by Shopee. In addition, promotion has a positive effect on impulse buying and acts as a moderation variable that reinforces the relationship between hedonistic lifestyles and impulse buying.